The Impact of Fermentation on the Physical and Chemical Properties of Green and Roasted Robusta Coffee Beans - Annisa Lutfi Alwi; Anni Nuraisyah; Rizky Nirmala Kusumaningtyas (Jurnal Penelitian Pendidikan IPA, 2026)
Conventional coffee decaffeination often relies on chemical solvents that can alter quality and raise processing costs. Although biological fermentation has been studied, research typically evaluates fermentation and roasting separately. Additionally, the use of civet-derived microorganisms as fermentation inoculants is less explored compared to spontaneous, yeast, or lactic acid bacteria-based fermentations. Therefore, this study investigated the interaction between civet-derived microbial inoculum and fermentation duration on the physicochemical characteristics of Robusta coffee before and after roasting. Fully ripe Robusta coffee cherries were fermented in sealed fermenters using civet-derived inoculum at 0%, 50%, and 100% concentrations for 24, 48, and 72 h under controlled conditions; each treatment was replicated 3 times. Density, moisture content, and caffeine concentration were determined in green and medium-roasted beans using standard methods and HPLC analysis. Fermentation significantly affected caffeine concentration and several physical properties of coffee beans. In roasted beans, caffeine content ranged from 0.20% to 0.34%, with the lowest value observed at 100% inoculum for 72 h and the highest at 50% inoculum for 24 h. Extended fermentation reduced caffeine by up to 35.3% (0.34% to 0.22%). These findings demonstrate that civet-derived microbial fermentation can serve as a sustainable biological decaffeination strategy while influencing coffee responses during roasting.